NEGOTIATING RELIGIOUS IDENTITY IN DIGITAL COMMUNICATION DISCOURSE: A Study of Acehnese Hijab TikTokers - Hakim, Putri Rahmah Nur; Abdullah, Irwan; ZA, Tabrani; Lestari, Annisa Dwi; Hasaniy, Nur Rif’ah (UIN Sumatera Utara, 2025)
This study examines how these creators actively negotiate religious identity within the algorithmic and performative structure of TikTok. Using a qualitative descriptive approach, data were collected through documentation of video content, captions, user comments, and online news, then analyzed thematically. The findings reveal that identity negotiation occurs through the strategic blending of Islamic markers such as hijab styles, Qur'anic phrases, modest aesthetics with local Acehnese cultural cues and popular TikTok formats including lipsync, short skits, and reflective storytelling. These dynamics highlight that religious identity online is co-constructed between creators and viewers. The study calls for strengthening digital religious literacy and encourages further research on gendered ethics and visual politics in contemporary Islamic expression.Keywords: Acehnese Muslimah, Digital Communication, Hijab Representation, Religious Identity, TikTok Narratives